응급구조(학)과 학생의 여성119구급대원에 대한 인식 유형 연구 : Q방법론적 접근 - Lee, Jaemin; Han, Seungtae; An, Juyeong (한국재난정보학회 논문집, 12(4), 2016)
This research is about Department of Emergency medical services students' cognition type of female 119 paramedics. The purpose of this research is to understand department of emergency medical servises students' cognition of female 119 paramedics and identify characteristics classified by types. To this end, applying Q-method, this research objectively analyzes 72 department of emergency medical services students' reaction who complete the field training about ambulance about female 119 paramedics. The result of the department of emergency medical services students recognized type of female 119 paramedics could be typed into four types. The type I is recognized as "Stamina limit type", the type II as "expert type", the type III as "guardian angel type", and the type IV as "feminine experience type". The type I has 28.3%, the type II has 12.7%, the type III has 6%, and the type IV has 3.8% explanation power, and these explain 51% of total variable. Generally department of emergency medical services students' cognition of female 119 paramedic is that they are expert in first aid but students' cognition is negative because of female 119 paramedic's limit of stamina, exposure to danger, and giving birth and infant care thus we should arrange solution of these cognition. 본 연구는 응급구조(학)과 학생이 인식하는 여성119구급대원에 대한 인식유형 연구이다. 본 연구의 목적은 응급구조(학)과 학생의 여성119구급대원에 대한 인식을 파악하고 유형별 특성을 확인하기 위해 시행되었다. 이를 위해, 본 연구에서는 Q 방법을 적용하여, 구급차동승 현장실습 교과목을 이수한 응급구조(학)과 학생 72명을 대상으로 여성119구급대원에 대한 주관적인 반응을 객관적으로 분석하였다. 연구결과, 응급구조(학)과 학생들의 여성119구급대원에 대한 인식유형은 네 가지로 유형화될 수 있었다. 제 I 유형은 '체력한계형', 제 II 유형은 '전문가형', 제 III 유형은 '수호천사형', 제 IV 유형은 '여성적 경험형'으로 인식되었다. 각각의 설명력은 제 I 유형 28.3%, 제II유형 12.7%, 제 III 유형 6%, 제IV유형은 3.8%로 전체변량의 51%를 설명하는 것으로 나타났다. 전체적으로 응급구조(학)과 학생의 여성119구급대원에 대한 인식은 응급처치에 대한 전문가이지만 체력적 한계, 위험성 노출과 출산 및 육아에 대하여 인식이 긍정적이지 못한 것으로 조사되어 해결방안이 마련되어야 할 것이다.